Hubungan Tingkat Stres dengan Kadar Gula Darah dan Penyembuhan Luka - Narullita, Dewi; Aro’fah, Suhaela; Budiman, Selamat; Z, Zahlimar; Hasan Basri, Muh (Pustaka Galeri Mandiri, 2025)
Diabetes mellitus is a chronic disease that is frequently accompanied by diabetic foot ulcers, which are characterized by delayed wound healing. In addition to metabolic factors, psychological conditions such as stress are believed to contribute to elevated blood glucose levels and impaired wound healing. This study aimed to analyze the relationship between stress levels, blood glucose levels, and wound healing among patients with diabetes mellitus in the Rimbo Tengah Public Health Center working area. This study employed a correlational analytic design with a cross-sectional approach. A total of 40 patients with diabetes mellitus were recruited using a purposive sampling technique. Stress levels were assessed using the Depression Anxiety Stress Scale (DASS-42) questionnaire, blood glucose levels were obtained from blood glucose measurements, and wound healing was evaluated using the Bates-Jensen Wound Assessment Tool (BWAT). Data were analyzed using the Spearman Rank correlation test with a significance level of 95% (? = 0.05). The results showed that most respondents experienced mild stress (52.5%), had poor blood glucose control (50.0%), and were classified in the wound regeneration category (57.5%). Bivariate analysis revealed a significant relationship between stress levels and blood glucose levels (p = 0.002; r = 0.462), as well as between stress levels and wound healing (p = 0.004; r = 0.418). Higher stress levels were associated with poorer glycemic control and slower wound healing. It can be concluded that psychological conditions play an important role in diabetes management and the wound healing process. Therefore, nursing care should integrate stress management as part of comprehensive interventions to improve glycemic control and accelerate wound healing in patients with diabetes mellitus.